2022
DOI: 10.3390/foods11040578
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy and Improved Inception Network for Determination of FHB-Infected Wheat Kernels

Abstract: Detection of infected kernels is important for Fusarium head blight (FHB) prevention and product quality assurance in wheat. In this study, Raman spectroscopy (RS) and deep learning networks were used for the determination of FHB-infected wheat kernels. First, the RS spectra of healthy, mild, and severe infection kernels were measured and spectral changes and band attribution were analyzed. Then, the Inception network was improved by residual and channel attention modules to develop the recognition models of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…132 RS combined with deep learning networks were recently used for the detection of Fusarium head blight (FHB)-infected wheat kernels. 133…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…132 RS combined with deep learning networks were recently used for the detection of Fusarium head blight (FHB)-infected wheat kernels. 133…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Raman spectroscopy was adopted to detect rot disease of maize caused by Colletotrichum graminicola , 130 rose rosette infection 131 and to investigate wheat and sorghum grains infected with ergot, black tip or mold 132 . RS combined with deep learning networks were recently used for the detection of Fusarium head blight (FHB)‐infected wheat kernels 133 …”
Section: Newly Developed Techniquesmentioning
confidence: 99%
“…While the NIR spectrometer consistently yielded the best results, the Raman spectrometer was nearly as accurate. However, using a 1064 nm laser instead of a 785 nm laser, as in most Raman and wheat‐related publications (Czaja et al, 2020; Qiu et al, 2022), could reduce the baseline and enhance prediction accuracy. The fluorescence spectrometer used for flour samples was unsuitable for long‐term measurements due to nonlinear changes in the light source spectrum, necessitating its replacement during the study.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is primarily based on the relative concentrations of metabolites present within a plant, namely Raman active molecules phytochemicals such as terpenes, phenolics, and alkaloids. For example, a study in 2022 showed that RS could detect Fusarium head blight in wheat kernels due to the spectral changes in bands associated with lignin, carotenoids, pectin, cellulose, protein, and starch ( Qiu et al., 2022 ). It was also recently demonstrated that RS could be used to diagnose nutritional deficiencies, salinity stress, and aluminum and iron toxicities with high accuracy in rice crops ( Sanchez et al., 2020 ; Higgins et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%